Diversifying institutional food procurement: opportunities and barriers for integrating biodiversity for food and nutrition in Brazil - Beltrame, Daniela M. de Oliveira; Oliveira, Camila Neves Soares; Borelli, Teresa; Santiago, Raquel de Andrade Cardoso; Monego, Estelamaris Tronco; Rosso, Veridiana Vera de; Coradin, Lidio; Hunter, Danny (Raízes: Revista de Ciências Sociais e Econômicas, 2016)
The Brazilian Food Procurement Program (PAA) and the National School Feeding Program (PNAE) were identified by the GEF-funded Biodiversity for Food and Nutrition Project (BFN)¹ as policy instruments with the greatest potential for diversifying institutional food procurement and improving diets while supporting family farming. This paper discusses the opportunities identified for mainstreaming biodiversity through PAA and PNAE, targeted activities undertaken as well as two case studies. The first case study presents findings linked to the implementation of the PNAE in quilombola communities in Goiás, while the second describes results of the inclusion of Juçara fruits (Euterpe edulis Mart.) in school meals in São Paulo. The paper concludes by highlighting some of the key barriers to better biodiversity mainstreaming and institutional food procurement together with some recommendations.